2022
DOI: 10.1007/s10546-021-00681-7
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between the Nocturnal Low-Level Jets and the Urban Boundary Layer: A Case Study over London

Abstract: Understanding the physical processes that affect the turbulent structure of the nocturnal urban boundary layer (UBL) is essential for improving forecasts of air quality and the air temperature in urban areas. Low-level jets (LLJs) have been shown to affect turbulence in the nocturnal UBL. We investigate the interaction of a mesoscale LLJ with the UBL during a 60-h case study. We use observations from two Doppler lidars and results from two high-resolution numerical-weather-prediction models (Weather Research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
(86 reference statements)
0
4
0
1
Order By: Relevance
“…Nevertheless, the ingress of transboundary aerosols into the PBL was not considered, which is a pivotal step in deteriorating ground‐level air quality via turbulent mixing (Geiß et al., 2017; Tang et al., 2016; Zhu et al., 2018). Furthermore, the mechanism during nighttime is complicated because nocturnal low‐level jet (LLJ) also plays a vital role in urban haze formation (Tsiringakis et al., 2022). More evidence is needed from direct observations of haze in the upper atmosphere to understand the interaction mechanism between transboundary haze and PBL.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the ingress of transboundary aerosols into the PBL was not considered, which is a pivotal step in deteriorating ground‐level air quality via turbulent mixing (Geiß et al., 2017; Tang et al., 2016; Zhu et al., 2018). Furthermore, the mechanism during nighttime is complicated because nocturnal low‐level jet (LLJ) also plays a vital role in urban haze formation (Tsiringakis et al., 2022). More evidence is needed from direct observations of haze in the upper atmosphere to understand the interaction mechanism between transboundary haze and PBL.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, cities can interact with local or even regional weather and climate, and change environmental conditions. In particular, studies have shown effects on atmospheric circulation, cloud cover, and precipitation (Lorentz et al 2019;Theeuwes et al 2019;Tsiringakis et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of thunderstorms induced‐hail events between 2014 and 2017 are reported within the Surabaya urban area (Figure 1) (Baskoro, 2017), suggesting that the urban area might induce or enhance a thunderstorm. Three mechanisms are associated to the modification of a storm over cities; (a) the urban heat island' effect (UHI)'s due to the modified urban surface radiation and energy balance (Lin et al., 2011; Ma et al., 2017), (b) the roughness effect of urban surface (D. Li et al., 2013; Bender et al., 2019; Tsiringakis et al., 2022) and (c) the urban aerosol effects (Yang et al., 2017). These three might trigger or enhance the convective cloud formation (Han et al., 2012), increase or modify the precipitation over and downwind of the city, (D. Li et al., 2013; Kim et al., 2021).…”
Section: Introductionmentioning
confidence: 99%